If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -8 = -2 + 3 Reorder the terms: -8 + x = -2 + 3 Combine like terms: -2 + 3 = 1 -8 + x = 1 Solving -8 + x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + x = 1 + 8 Combine like terms: -8 + 8 = 0 0 + x = 1 + 8 x = 1 + 8 Combine like terms: 1 + 8 = 9 x = 9 Simplifying x = 9
| 6+17y=15+14y | | 5(6k-5)+4=12-3k | | -8(x-4)=2(x+6) | | 3+2k=7 | | w/3+5=10 | | -28+15+-22z=31 | | 20x-20=15x-20 | | x^4+2x^2=3 | | -8.4=k+0.6 | | 3x+2(5/4x-3/4)=4 | | 5x+10+7(x-2)=180 | | -10=-5/7x | | 3+9q=9+4q | | 4x+5=43/5 | | a-5.1=1.7 | | (2+x)+3=7 | | -4(1+m)=2+2m | | (x17)/72=17 | | 8x+3=32 | | x^2(1200-x^2)/(4x) | | -31=z+(-17) | | -7+r/6=-6 | | 42j+8-18=-28 | | 7(-1+5n)=-7+8n | | 3/8=r/2/3 | | 3(1)-4y=3 | | -14x+6-10x+30=64 | | x^2(1200/4x-x^2/4x) | | -2/5(x+5)-3=65 | | -5(2x+3)=-7x-33 | | (5x-6)-(6x-3)=-(-3+x)-3x+6 | | 6x+3=-63 |